2012
DOI: 10.1080/07448481.2012.673519
|View full text |Cite
|
Sign up to set email alerts
|

“That's So Gay!”: Examining the Covariates of Hearing This Expression Among Gay, Lesbian, and Bisexual College Students

Abstract: College professionals and student leaders must acknowledge that the phrase is a form of heterosexist harassment. As such, policies addressing diversity and harassment should address students' use of this phrase, aiming to reduce its use. Additionally, colleges and universities should develop practices that counteract poorer well-being associated with hearing the phrase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 34 publications
5
79
0
Order By: Relevance
“…At the bivariate level, significant moderate correlations (not reported) were found between each form of discrimination and each outcome in the anticipated direction; the regression models similarly demonstrated that victimization and microaggressions related to greater forms of psychological distress (lower self-esteem; greater perceived stress and anxiety symptoms). These findings are in line with previous research looking at multivariate relationships between victimization and/or microaggressions and well-being (Silverschanz et al, 2008;Woodford et al, 2012;Woodford, Han et al, 2014;Woodford, Kulick et al, 2014). The documented significant positive relationships between microaggressions, self-esteem, perceived stress, and anxiety likely reflect the stressors inherent within microaggressions.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…At the bivariate level, significant moderate correlations (not reported) were found between each form of discrimination and each outcome in the anticipated direction; the regression models similarly demonstrated that victimization and microaggressions related to greater forms of psychological distress (lower self-esteem; greater perceived stress and anxiety symptoms). These findings are in line with previous research looking at multivariate relationships between victimization and/or microaggressions and well-being (Silverschanz et al, 2008;Woodford et al, 2012;Woodford, Han et al, 2014;Woodford, Kulick et al, 2014). The documented significant positive relationships between microaggressions, self-esteem, perceived stress, and anxiety likely reflect the stressors inherent within microaggressions.…”
Section: Discussionsupporting
confidence: 91%
“…Past studies have documented forms of subtle heterosexist behaviors, including gay jokes and other slurs (Silverschanz, Cortina, Kornik, & Magley, 2008) and the microaggression "that's so gay" (Woodford et al, 2012). While not always labeled as microaggressions, recent work has documented examples of subtle discrimination affecting trans* people in college, such as facing unreasonable barriers to changing one's name or gender on campus records (Seelman, 2013) and witnessing others minimize the need for changing policies to protect trans* people (Case, Kanenberg, Erich, & Tittsworth, 2012).…”
Section: Experiences Of Discrimination Impacting Lgbtq College Studentsmentioning
confidence: 99%
See 3 more Smart Citations